Brand Ambassador dan Marketplace terhadap Minat Konsumen pada Produk Fashion - Nia Sonani; Harmoko Sukayat; Angga Pramadista Sudrajat; Sarlina Sari (IPM2KPE, 2023)
This study aims to determine the influence of brand ambassadors and marketplaces on consumer interest in fashion products. This research method is quantitative. The research was conducted on students of the Accounting Study Program at STIE PGRI Sukabumi and obtained 54 respondents. Hypothesis testing using the validity test for all questionnaires was declared valid and the reliability test was declared reliable. The analysis performed is regression analysis, coefficient of determination, and t test. The results showed, a) the brand ambassador variable on consumer interest had a significance level of 0.001 <0.05 and tcount 2.556 > 2.009; b) the marketplace variable on consumer interest has a significance level of 0.000 <0.05 and tcount 2.361 > 2.009; c) F-count value of 8.065> from F-table of 3.18; d) the coefficient of determination (R2) is 0.623, meaning that the percentage of brand ambassadors and marketplace influence on consumer interest in fashion products is 62.3% and the remaining 37.7% comes from other variables not examined. Conclusion, a) partially brand ambassadors have a positive and significant effect on consumer interest in fashion products; b) partially, the marketplace has a positive and significant effect on consumer interest in fashion products; c) simultaneously brand ambassadors and marketplaces have a significant positive influence on consumer interest in fashion products. Keywords: Brand Ambassador, Marketplace, Consumer Interest